A new species of Drypetes (Putranjivaceae/Euphorbiaceae s.l.) from West Bengal, India - Krishna, Gopal; Karthigeyan, K.; Arisdason, W.; Chakrabarty, T. (Phytotaxa, 2017)
A new species, Drypetes kalamii, collected from the subtropical forests of two different Protected Areas, Buxa National Park and Jaldapara National Park in the state of West Bengal, India, is described and illustrated. This new species closely resembles Drypetes ellisii, but differs in being small shrub (female plants) or scrambling shrub (male plants) with corrugated branches and puberulous branchlets, longer petioles, laminae abruptly acuminate with pointed apices, slender and puberulent fruiting pedicels with bracts and bracteoles and smaller, ovoid-globose drupes.